Clinical Spectrum and Drug Sensitivity Pattern in Multi Drug-Resistant Typhoid Fever - Afzal, Warda; Saba, Ameena; Zaidi, Syed Taqi Hasan; Siddiqui, Hamid Jamal; Tahir, Muhammad (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To study the clinical presentation, complications and drug sensitivity patterns of multi drugs- resistant enteric fever.Study Design: Prospective longitudinal study.Place and duration of study: Combined Military Hospital, Malir Cantt Karachi Pakistan, from Mar to Oct 2019.Methodology: A hundred cases of multi-drug resistant enteric fever were enrolled. Their demographic data, clinical and laboratory features and drug sensitivity pattern was recorded.Results: Out of 100 cases, 67 were within 5 to 11 years of age. Twenty-one patients presented with loose motion and splenomegaly each. Seventy cases had a fever of 1 to 2-weeks duration. Complications were seen in 42 cases, out of which hepatitis was most commonly observed (in 27 cases). Ciprofloxacin and Ceftriaxone sensitivity were found to be only 3% and 9%, respectively. Sensitivity to Azithromycin was 95%, while all cases were sensitive to Meropenem and Imipenem.Conclusion: Very high frequency of extensively drug-resistant typhoid fever was found. Most cases of enteric fever had a fever as the only presenting feature. Typhidot test has very low sensitivity.